Peran Guru Dalam Menggunakan Media Pembelajaran Interaktif Untuk Membangun Motivasi dan Minat Belajar Siswa - Ahnaf Istiqlal Berutu; Mafira Roza; Riki Naldi Hsb (Universitas Maritim AMNI Semarang, 2024)
In learning, the teachers job is to educate, teach, lead and evaluate students. Learning can be done with learning alat that is more innovative and productive in presenting the material presented to students in class. The utilization of interactive learning alat is expected to have a major contribution and innovation in the world of education. With the interactive learning alat, it is expected to make it easier for teachers to create innovative and senang learning so that student motivation and interest in learning can increase. Motivation is the basic driving force that encourages a persons learning activities so that he is interested in something he is learning, because interest is a motivational tool in learning. A persons interest in learning depends on how much he wants to get learning results. How important the role of the teacher is in the use of this interactive learning alat, therefore the use of alat has a very big influence on increasing student motivation and interest in learning.